2012
DOI: 10.1177/0022219411436214
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and Stability of Mathematics Skill and Difficulty

Abstract: The present study evaluated the stability of math learning difficulties over a 2-year period and investigated several factors that might influence this stability (categorical vs. continuous change, liberal vs. conservative cut point, broad vs. specific math assessment); the prediction of math performance over time and by performance level was also evaluated. Participants were 144 students initially identified as having a math difficulty (MD) or no learning difficulty according to low achievement criteria in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 93 publications
(141 reference statements)
7
29
0
Order By: Relevance
“…To compare students with and without MD, we split the 500 students into two groups based on performance on a measure of addition fluency (e.g., Powell et al., in press). This method for identification of students with MD is in line with current MD research practices (e.g., Martin et al., ; Powell & Fuchs, ). Students ( n = 108) scoring at or below the 21st percentile (i.e., 7 or fewer correct answers on Addition Fluency ) were categorized as MD; students ( n = 305) scoring at or above the 43rd percentile (i.e., 11 or more correct answers on Addition Fluency ) were categorized as typical performers.…”
Section: Methodsmentioning
confidence: 61%
See 1 more Smart Citation
“…To compare students with and without MD, we split the 500 students into two groups based on performance on a measure of addition fluency (e.g., Powell et al., in press). This method for identification of students with MD is in line with current MD research practices (e.g., Martin et al., ; Powell & Fuchs, ). Students ( n = 108) scoring at or below the 21st percentile (i.e., 7 or fewer correct answers on Addition Fluency ) were categorized as MD; students ( n = 305) scoring at or above the 43rd percentile (i.e., 11 or more correct answers on Addition Fluency ) were categorized as typical performers.…”
Section: Methodsmentioning
confidence: 61%
“…In this article, we categorized students falling at or below the 21st percentile on Addition Fluency as students with MD. Typical cut‐scores for determining mathematics difficulty include students scoring at or below the 40th percentile (e.g., Jitendra et al., ), 32nd percentile (e.g., Martin et al., ), 25th percentile (e.g., Bryant et al., ; Fuchs et al., ), or 10th percentile (Geary, Hoard, Nugent, & Byrd‐Craven, ). Despite not having an agreed upon cut‐score in MD research, at or below the 21st percentile on fact retrieval based assessments is a stringent cut‐score in line with current literature.…”
Section: Methodsmentioning
confidence: 99%
“…Behavioral EFs. Although researchers have shown that adolescents (Swanson, 2012) and primary school children (Martin et al, 2012;Raghubar et al, 2009;Wu, Willcutt, Escovar, & Menon, 2014) with MD have more problems with teacher-and parent-rated attention behaviors than their peers with average or higher mathematics scores, other behavioral EFs among students with MD are not understood. Significant relations between parent- (Wu et al, 2014) and teacherrated (Fuchs et al, 2006;Martin et al, 2012;Raghubar et al, 2009) attention behaviors and mathematics performance were found but only in primary school.…”
Section: Efs and Mathematics Performancementioning
confidence: 99%
“…Nevertheless, when the documents were read with Adobe Acrobat XI Pro's Read Out Loud feature, all articles, including those that were not tagged were read in the correct reading order. Taking one article as an example, the NVDA screen reader did not have problems interpreting the article by Martin et al (2013) which was tagged and where all the elements were tagged, with the document having a logical reading order. This confirms the benefits of appropriate tagging.…”
Section: Findings From Accessibility Testing With Nvda and Adobe Acromentioning
confidence: 99%
“…Although the article by Martin et al (2013) did not pass the test for logical reading order with PAC 1.3, which showed a warning for this criterion, it had a better tag structure (Fig. 4), as the whole content in the document was represented in the tag structure in a logical way and could be read logically with NVDA.…”
Section: Findings From Accessibility Testing With Nvda and Adobe Acromentioning
confidence: 99%